Patogenisitas Beberapa Isolat Beauveria Bassiana pada Plutella xylostella - Suharto Suharto (Universitas Gadjah Mada, 2004)
Plutella xylostella (L.) (Lepidoptera : Plutellidae) is key pest on cabbage. P. xylostella can be infected by Beauveria bassiana from other insects. The objective of this study was to determine the pathogenicity five isolates of B. bassiana on P. xylostella. Those isolates were BbUj1 (larvae of Lepidoptera), BbUj2 (rice brown plant hopper), BbUj3 (rice brown plant hopper), BbUj4 (rice seed bug), and BbUj5 (rice black bug). In the laboratory every isolate was inoculated 5 µL spore suspension at rate 107 spores/mL to third instar P. xylostella larva used micro liter syringe. Each treatment used 10 larvae and was replicated five times. The pathogenicity of B. bassiana was determined based on mortality and LT50 value. The potential isolate was tested to find LC50 subsequently tested on cabbage crop in the green house. The result of the study showed that BbUj1 from larvae of Lepidoptera was the potential isolate with LC50 of 9.49 x 10^5 spores/mL. LT50 was 2.67 days for the concentration 107 spores/mL. Green house application of B. bassiana at rate of 5 x 10^12 spores/ha caused 57 percent mortality of P. xylostella larva in seven days after treatment and LT50 was 5.67 days.